Visions for small-scale renewable energy production on Finnish farms – A Delphi study on the opportunities for new business - Rikkonen P.; Tapio P.; Rintamäki H. (Elsevier Ltd, 2022)
The processes of molt and reproduction, and the overlap of the two during a bird's life, are practically unstudied in most tropical environments in South America, especially in Peruvian Amazonia. Our study contributes to understanding these processes in this Neotropical region by analyzing data on molt and reproduction of the understory avifauna and their relationship to different biotic environmental (flowering and fruiting) and abiotic factors (precipitation, temperature) during one year in the Allpahuayo Mishana National Reserve in northeastern Peru. A total of 1556 individuals, belonging to 108 species, were captured, of which 847 were molting. Likewise, only 89 individuals were found with a fully vascularized brood patch. However, the level of overlap with molting was high, as a total of 44 (49%) of the birds with a brood patch were also molting primaries. We found that both molt and reproduction occurred throughout the year, with peaks in June-July (the less rainy season) and October-November (the beginning of the rainy season). There was a positive correlation between molt and breeding, and a negative correlation between the presence of juveniles and the fruiting of woody plants. However, we found no statistically significant correlation of molt or reproduction with precipitation, temperature, flowering, and fruiting seasons of woody plants. These results may be subject to the influence of climatological factors and the availability of food resources, such as arthropods, that were not covered in this study. Furthermore, inference is limited due to the relatively short time frame of the study.